PENGARUH KEAKTIFAN BERORGANISASI, KEIKUTSERTAAN UKM, DAN KONDISI EKONOMI TERHADAP PRESTASI AKADEMIK MAHASISWA PRADITA: STUDI PADA ANGGOTA ORGANISASI & UKM PERIODE MASA JABATAN 2023/2024 - Joseph Evan Prabadhi; William Widjaja (Jurnal Nusa Manajemen, 2026)
In the context of higher education, academic achievement serves as a key indicator of students’ success in the learning process. This achievement reflects the outcomes individuals attain through their cognitive, emotional, and behavioral efforts. This study aims to examine the influence of organizational involvement, participation in Student Activity Units (UKM), and economic conditions on the academic performance among Pradita University Students during the 2023/2024 Term.. A quantitative approach was employed using a survey of 41 respondents who were active members of both campus organizations and UKM. The data were analyzed using SEM-PLS with SmartPLS 4. Respondents were selected through purposive sampling based on the criterion of being involved in campus organizations and UKM during the 2023/2024 period. The findings indicate that organizational involvement and economic conditions have a significant positive effect on academic performance, whereas participation in UKM does not show a significant impact. The research model explains 43% of the variance in academic performance, reinforcing that external factors such as organizational activity and economic stability play an important role in supporting students’ academic success.